Arabic Language Learning based on Multiple Intelligences - Irmansyah, Irmansyah; Gustan, Feby Febrianti; Mukmin, Mukmin (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2025)
This study aims to: 1) To explain the learning of mahārah al-qirā’ah at MI Nurul Qomar Palembang. 2) To explain the learning of mahārah al-qirā’ah based on multiple intelligences using the book of mutholaah alhaditsah volume I at MI Nurul Qomar Palembang. 3) To explain the effectiveness of learning mahārah al-qirā’ah based on multiple intelligences using kitab mutholaah alhaditsah volume I at MI Nurul Qomar Palembang. This research uses a combination research method between qualitative and quantitative approaches or better known as Mixed Method. Data collection techniques in this study were carried out through several stages such as observation, interviews, documentation and tests. The data collected in this study will be processed and analyzed by combining two methods, namely qualitative analysis to explore deep insights and quantitative analysis to measure the results objectively. This study shows that the previously applied maharah qiraah learning was relatively ineffective in improving students’ understanding, thus requiring a breakthrough in the use of methods and media to make learning more effective and capable of enhancing students’ comprehension. The Asymp. Sig (2-Tailed) value obtained in this study is 0.000 < 0.05. Therefore, it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, meaning there is an improvement in students’ maharah qiraah skills after implementing multiple intelligences-based maharah qiraah learning using the Mutholaah Alhaditsah Volume 1 book at MI Nurul Qomar Palembang. يهدف هذا البحث إلى: ١) لمعرفة تعليم مهارة القراءة في المدرسة نور القمر الإبتدائية بالمبانج. ٢) لمعرفة تعليم مهارة القراءة على أساس الذكاءات المتعددة باستخدام كتاب المطالعة الحديثة ١ في المدرسة نور القمر الإبتدائية بالمبانج. ٣) لمعرفة فعالية تعليم مهارة القراءة على أساس الذكاءات المتعددة باستخدام كتاب المطالعة الحديثة ١ في المدرسة نور القمر الإبتدائية بالمبانج. يستخدم هذا البحث أسلوب بحث يجمع بين المنهجين الكيفي والكمي أو ما يعرف بالمنهج المختلط. تم تنفيذ تقنيات جمع البيانات في هذا البحث من خلال عدة مراحل مثل الملاحظة والمقابلات والتوثيق والاختبارات. ستتم معالجة البيانات التي تم جمعها في هذا البحث وتحليلها من خلال الجمع بين طريقتين، وهما التحليل الكيفي لاستكشاف الرؤى العميقة والتحليل الكمي لقياس النتائج بموضوعية. يشير هذا البحث إلى أن طريقة تعليم مهارة القراءة التي تم تطبيقها سابقًا تميل إلى أن تكون أقل فعالية في تحسين فهم الطلاب، مما يتطلب ابتكارًا جديدًا في استخدام الأساليب والوسائط التعليمية حتى تصبح أكثر فعالية وقادرة على تحسين فهم الطلاب. النتيجة التي تم الحصول عليها في هذا البحث هي 0.000 < 0.05. وبالتالي، يمكن استنتاج أن الهاء مقبولة والهاء مرفوضة، مما يعني أن هناك زيادة في قدرة الطلاب على القراءة بعد تطبيق تعليم مهارة القراءة على أساس الذكاءات المتعددة باستخدام كتاب المطالعة الحديثة ١ في المدرسة نور القمر الإبتدائية بالمبانج.